PENGARUH SEKTOR – SEKTOR POTENSIAL TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN SIDOARJO - Sephen Dwi Aura; Kiky Asmara (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research was conducted to know which sectors are potential sectors and how they affect the increase in Regional Original Income in Sidoarjo Regency. The data used in this study was secondary data from the year 2011 to 2020 sourced from the Central Statistics Agency. To find out which sectors are potential sectors, the Location Quotient (LQ) method was used. To find out the growth that occurs in the Sidoarjo Regency and East Java Province, The Shift-Share method was used. Meanwhile, to calculate the effect on Regional Original Income, the method of multiple regression analysis was used. This study has three findings, first, Sidoarjo Regency has four potential sectors, namely Gas Electricity Procurement; Transportation and Warehousing; Processing Industry; and Construction. Second, a sector that has fast national growth and strong competitiveness against economic growth. Based on PR calculations, from 2011 to 2020, Sidoarjo Regency has 8 sectors driving the growth of the same sector at the provincial level. Based on PS calculations, from 2011 to 2020, Sidoarjo Regency has 9 sectors driving the growth of the same sector at the provincial level.Based on DS calculations, from 2011 to 2020, Sidoarjo Regency has 6 economic sectors with good locational advantages. Third, the potential sectors that have an influence on increasing PAD are the Electricity and Gas Procurement sector and the Construction sector.